Implementation of GUI in the determination of critical clearing angle using the OMIB and equal area criterion - Salim N.A.; Abd Samat A.A.; Othman M.M.; Mohamad H.; Ab Aziz N.F.; Rahmat N.A. (Engineering and Scientific Research Groups, 2023)
Electric equipment protection; Graphical user interfaces; Large scale systems; Reactive power; System stability; Transients; Critical clearing angle (CCA); Dynamic equivalent models; Equal area criterion; Graphical user interfaces (GUI); One-machine infinite bus; One-machine-infinite-bus systems; Power system networks; Transient stability analysis; Electric power system protection